If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + 12 = 2p + -4 Reorder the terms: 12 + 6p = 2p + -4 Reorder the terms: 12 + 6p = -4 + 2p Solving 12 + 6p = -4 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. 12 + 6p + -2p = -4 + 2p + -2p Combine like terms: 6p + -2p = 4p 12 + 4p = -4 + 2p + -2p Combine like terms: 2p + -2p = 0 12 + 4p = -4 + 0 12 + 4p = -4 Add '-12' to each side of the equation. 12 + -12 + 4p = -4 + -12 Combine like terms: 12 + -12 = 0 0 + 4p = -4 + -12 4p = -4 + -12 Combine like terms: -4 + -12 = -16 4p = -16 Divide each side by '4'. p = -4 Simplifying p = -4
| 135.7*10= | | 18-5x(2+3)= | | 12x^2+13x+14=0 | | 88-4x=23x+16 | | 48r^2-27=0 | | 14-8x=169-43x | | 7+2z=5+11z | | 5x+5x+5x=15 | | 9x^2+54x-18=0 | | 9j^2-3j+2j^3= | | 4y^2+11y+121=0 | | -5x^2+40x+0=0 | | -22=-2x | | y^2+30=-11y | | -5(x+7)+x=6(2-x) | | x(x-5)=x^2+8x+4 | | 5u^2-14u-3=0 | | 0.2(y+3)+3=0.1(7y-4)-5 | | 6=11-2x | | 4x+14=x+11 | | z^2-3z-270=0 | | x*2=-x+7 | | 3-4x=-11 | | 3a^4b+24ab^4+48a= | | 3x^2-8x+13=0 | | 72x^6y^3+24x^2y^7= | | 3y+30= | | 10x-2(x-8)=8(x+1)+7 | | 6a+6(4)=0 | | 14x+13x-40=11 | | 110x^5+30x^7+60x^9= | | (a-b)(a+b)(b-c)(d+c)(c-a)(c+a)=0 |